Evaluating the Complex: Alternative Models and Measures for Evaluating Collaboration among Substance use Services with Mental Health, Primary Care and other Services and Sectors. Issue 1 (February 2014) - Rush, Brian
Many planners and administrators now look to "collaboration" or "integration" as a solution, or at least a partial solution, to challenges related to access and delivery of substance use and mental health services and health services in general. Among the major constraints in identifying best practices in this area and recommending optimal evaluation strategies are the plethora of terms and concepts used in the literature to describe collaboration or integration as well as the many alternative approaches and outcome expectations. It is helpful, therefore, to follow concrete steps to plan the evaluation, including the engagement of multiple stakeholders in the planning process and subsequent execution of the evaluation. The concrete evaluation strategies employed can follow a traditional, often linear model, of impact and are often categorized under the common typologies of process, outcome or economic evaluations. Each approach examines different domains of interest and can be at the individual/service level or at the level of the overall treatment system. Other less traditional evaluation models and methods based on systems theory, complex adaptive systems and developmental evaluation have much to offer the evaluation of interventions aimed at improving the collaboration and integration of substance use services with other health and social services and sectors. Realist evaluation is a particularly helpful approach that integrates many of the traditional approaches with these other models and methods.